Reaching the top but not feeling on top of the world: Examining women’s internalized power threats - Feenstra, Sanne; Begeny, Christopher T.; Jordan, Jennifer; Ryan, Michelle K.; Stoker, Janka I.; Rink, Floor A. (Frontiers in Psychology, 2022)
More and more women are breaking the glass ceiling to obtain positions of power. Yet with this rise, some women experience threats to their power. Here we focus on women’s perceived threats to the stability of their power and the degree to which women feel they do not deserve their power positions, as reflected in their impostor feelings. The present research identifies key workplace characteristics that are associated with these internalized power threats with survey data collected among 185 women in high-power positions. We find that negative workplace experiences (i.e., gender discrimination, denigrating treatment, lack of cultural fit, and lack of mentoring) are associated with a greater sense of power threat, which in turn relates to adverse workplace outcomes (i.e., reduced job satisfaction and increased emotional exhaustion and opting-out intentions). With this unique sample of high-powered women, our findings help illustrate the forces that make women experience power as precarious, thereby shedding light on the disadvantages these women face. We provide suggestions on how to reduce women’s internalized power threats.